2009
DOI: 10.1007/s00415-009-5257-5
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology of MS: results from the German MS Registry

Abstract: Since 2002, an MS Registry has been implemented by the German MS Society in more than 100 German MS centres. The objective is to provide information about disease characteristics, and to monitor the health care situation in a large population of patients. The aim of this report is to give detailed results on MS symptoms. By October 2008, data sets from 16,554 patients were recorded by 86 centres. A strikingly high number of persons suffered from fatigue and other "invisible" symptoms during early and late stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 9 publications
3
51
0
12
Order By: Relevance
“…This data set was based on the minimal data set of the German MS register, which has been run by the German MS society (DMSG Bundesverband e.V.) since 2001 [5][6][7]16], and was modified due to the suggestions of SAC members. In addition, the socioeconomic aspects and the EQ5d were derived from several well-designed cost-of-illness-studies [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…This data set was based on the minimal data set of the German MS register, which has been run by the German MS society (DMSG Bundesverband e.V.) since 2001 [5][6][7]16], and was modified due to the suggestions of SAC members. In addition, the socioeconomic aspects and the EQ5d were derived from several well-designed cost-of-illness-studies [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…15 It remains difficult to conduct adequate needs assessment, as there is still no single, unambiguous, clear definition for the term 'severe MS.' 16 The most commonly used instrument to evaluate the severity of affectedness, the EDSS (Expanded Disease Status Scale), 17 assesses patients' functional status, referring primarily to restriction of movement, not other symptoms relevant for the severity of MS (e.g., fatigue, depression, pain, visual dysfunction). 18,19 Patients' own subjective definitions of being severely affected fit with the palliative approach, where intervention is guided by the subjective assessment of suffering. 16,20 Our study addresses this by exploring the unmet needs of MS patients in Germany who reported feeling severely affected.…”
mentioning
confidence: 99%
“…Problems with urination are common among people with MS [36,37], and it is wellknown that this has a great impact on quality of life and participation and are associated with mood disorders and fatigue [38,39].…”
Section: Discussionmentioning
confidence: 99%